The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.ajpath.2011.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Stabilizes Mitotic Cyclins and Prevents Cell Cycle Progression via Inhibition of UBE2C in Colorectal Carcinoma

Abstract: Substantial evidence implicates the ubiquitin-conjugating enzyme E2C (UBE2C) gene, in several human cancers, including colorectal carcinoma (CRC). We therefore investigated the prognostic value of UBE2C alterations in CRC and UBE2C signaling in CRC cell lines. UBE2C protein expression and UBE2C gene copy number were evaluated on clinical samples by immunohistochemistry and fluorescence in situ hybridization in a TMA format. The effect of the proteasome inhibitor bortezomib and small-interfering RNA knockdown w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Despite the fact that several preclinical trials have shown that bortezomib may be useful for the treatment of colorectal cancer, by inhibition of UBE2C [77] and increasing the CDK inhibitor p27 Kip1 [78], up to now, the results in the clinical setting have been disappointing (Table 1).…”
Section: Bortezomib In Colorectal Cancermentioning
confidence: 93%
“…Despite the fact that several preclinical trials have shown that bortezomib may be useful for the treatment of colorectal cancer, by inhibition of UBE2C [77] and increasing the CDK inhibitor p27 Kip1 [78], up to now, the results in the clinical setting have been disappointing (Table 1).…”
Section: Bortezomib In Colorectal Cancermentioning
confidence: 93%
“…Interestingly, UBE2C is nearly undetectable in normal tissues, at both the RNA or protein levels. In contrast, increasing evidence indicates that UBE2C protein is overexpressed in many human tumor types, including brain tumors (10), malignant breast carcinomas (11), lung cancer (12,13), anaplastic thyroid carcinomas (14), esophageal adenocarcinomas (15), hepatocellular carcinomas (16) and colorectal cancer (1719), suggesting that UBE2C may play an important role in tumorigenesis and progression. UBE2C overexpression causes the centrosome duplication instability, and variety of proteins can cause this phenomenon, including the anaphase-promoting complex (APC/C) substrates cyclin B, AURKA and PLK1 (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid proteasomal degradation of CKIs in subsequent cell cycle phases contribute to the uncontrolled cell division in cancer cells. Recent studies have established the involvement of ubiquitin proteasome pathway (UPP) in degradation and recycling of the above mentioned class of proteins, crucial for cancer onset and progression [29]. The proteasomal degradation of proteins is well complemented by the ubiquitin conjugating enzymes E1, E2 and E3 ligases, which add multiple ubiquitin molecules to the proteasome substrate proteins.…”
Section: Introductionmentioning
confidence: 99%